AUDIT COMMITTEE CHARACTERISTICS AND FINANCIAL PERFORMANCE OF QUOTED INSURANCE COMPANIES IN NIGERIA (American Journal of Business Management, Economics and Banking, 2024)
The study investigated audit committee characteristics and financial performance in Nigerian insurance companies. The study adopted ex-post-facto research design. Utilizing data from eleven insurance companies listed on the Nigerian Exchange Group as at 31st December, 2023, the study employed purposive sampling to ensure comprehensive analysis. Descriptive statistics and Ordinary Least Squares regression analysis, facilitated by E-view-9 statistical package, are utilized for rigorous examination. Results revealed a significant positive association between audit committee size, composition, and Profit After Tax (PAT). However, the frequency of audit committee meetings revealed positive insignificant relationship with PAT. The findings underscored the importance of diverse and expert audit committee members, structured meeting schedules, and continuous training programs to enhance governance effectiveness and drive financial performance in the Nigerian insurance sector.